KAJI NUMERIK GROUND PAD SHOE KENDARAAN TEMPUR DENGAN MODEL MATERIAL HYPERELASTIC - Rachmat, Angki Apriliandi; Dirgantara, Tatacipta; Suweca, I Wayan; Mardiyati, Yati (Faculty of Mechanical and Aerospace Engineering, 2024)
One of the important components on a combat vehicle is the ground pad shoe (GPS) or track pad. GPS that has been developed at this time mostly uses rubber material. Rubber raw materials themselves are found in Indonesia in large amount. Indonesia left 3 million tonnes of natural rubber unprocessed in 2018. On the other hand, natural rubber research is quite expensive and takes a long time to become a product. To make rubber products is needed special molds and tests. To solve the high costs and long time involved in rubber research, it is necessary to carry out numerical research. In this study, a numerical study of GPS rubber for combat vehicles was carried out with a hyperelastic material model. The research was conducted experimentally and numerically. Tensile testing is carried out on imported GPS samples which are then used as comparison data for numerical studies. The Mooney-Rivlin, Neo-Hookean, Yeoh, and Ogden hyperelastic models were varied to get the stress and strain values ​​closest to the experimental test. The results of the numerical study show that the best hyperelastic model for the imported GPS rubber model is the Neo-Hookean model. The tensile strength of GPS according to the experimental tensile test results is 16.93 MPa, while the result of the finite element method (FEM) is 16.75 MPa. The GPS modulus 200% according to the experimental tensile test results is 14.7 mm/mm, while the FEM result is 15.3 mm/mm. The difference between the FEM and experimental test values ​​for tensile strength and modulus 200% are below 5%. Maximum stress on GPS is 4,4 MPa and safety factor 3,8.